Raw data for "Hundt et al., Direct observation of the molecular mechnism underlying protein polymerization, Science Advances 2022" - Hundt, N; Cole, D; Hantke, M F; Miller, J J; Struwe, W B; Kukura, P (University of Oxford, 2022)
See "Actin_manuscript_ORA/Readme.txt" and "Actin_manuscript_ORA/Raw_videos_and_MP_analyses/Comments.txt".